Balint-style reflective practice groups in a year 4 undergraduate general practice attachment: experience of the first two years. Issue 2 (May 2020) - Richards, Helen; Polnay, Adam; Wilkinson, Peter; Read, Elizabeth; Young, Hilary
Background and aims: Many undergraduate medical curricula include reflective practice sessions based on traditional Balint-groups. Those sessions can help students to acknowledge that experiencing 'negative' feelings in relation to patients is normal and may contain important information about the clinical encounter. They may also help to protect students from some of the emotional challenges of studying medicine. The Edinburgh University scheme provides all students in their first clinical year with two dedicated reflective practice sessions. Here we report on experience of the first two years. Methods: Students' attitudes to the sessions were ascertained using a questionnaire, and views of the group leaders were assessed using a questionnaire and through informal verbal and email discussions. Practical difficulties were recorded as they arose. Results: Students generally rated the sessions positively with regard to exploring relationships and self-reflection, and they found the sessions interesting and helpful. The sessions did not seem to affect career choice. The free-text comments suggested four positive themes and four areas for future modification. Conclusion: We have succeeded in providing all undergraduate students with an opportunity to take part in a reflective practice. We have highlighted aspects which have been successful and suggested future improvements.